Keanekaragaman Crustacea Ordo Decapoda Di Kawasan Mangrove Pangkal Babu Desa Tungkal 1, Tanjung Jabung Barat - Fitriya Shalehati; Winda Dwi Kartika; Jodion Siburian; Tia Wulandari; Nurul Oktaviani (Jurnal Biologi Universitas Andalas, 2023)
Mangrove area is a type of ecosystem with unique characteristics. Mangrove ecosystems are located in brackish waters which are a meeting place between land and sea. Mangroves have an ecological function as a habitat for various types of fauna. In addition, many mangrove areas have been developed as ecotourism areas which have impacts on the environment such as the risk of damage to existing natural resources and the survival of one of the fauna that makes up the mangrove ecosystem, namely Crustaceans. The purpose of this study was to identify the diversity of Crustaceans of the Decapoda Order in the mangrove area of Tungkal 1 Village, Tanjung Jabung Barat. This research method is descriptive quantitative. Sampling was carried out exploratively using purposive sampling technique. Sampling was carried out at three stations using four types of fishing gear, namely spread nets, gill nets, sondong and togok carried out 3 repetitions on different days. The research results obtained found 15 species from 8 families including 10 species of shrimp and 5 species of crabs. The diversity index obtained as a whole is in the medium category and dominance index at each station is included in the low category.